Tropical Tongues : Language Ideologies, Endangerment, and Minority Languages in Belize - Gómez Menjívar, Jennifer Carolina; Salmon, William (Book collections on Project MUSE., 2018)
"In the period following the country's independence in 1981, Kriol has risen to the level of a national language. While the prestige enjoyed by English and Spanish is indisputable, a range of historical and socio-economic developments has given Kriol an elevated status in the coastal districts at the potential expense of more vulnerable minority languages also spoken there. Using fieldwork, ethnographic observations, interviews, and surveys of language attitudes and use, Gómez Menjívar and Salmon show the attenuation of Mopan and Garifuna alongside the stigmatized yet robust Kriol language. Examin[es] how large-scale economic restructuring can unsettle relationships among minority languages"--